PRAGUE QUADRENNIAL: SPACE AND SCENE DESIGN - Scheffler, Ismael; de Araújo, José Sávio Oliveira; Muniz, Rosane; Dias Massa, Clóvis (Cena, 2020)
Presentation of articles from issue 30 of the periodical, the first part of the dossier that addresses themes around the 14th edition of the Prague Quadrennial: Space and Scene Design, 2019.